From Mahidol University Journal of Pharmaceutical Sciences to Pharmaceutical Sciences Asia, From MUJPS to PSA - Mullika Traidej Chomnawang (Faculty of Pharmacy, Mahidol University, 2022)
Mahidol University Journal of Pharmaceutical Sciences (MUJPS) was first published in 1974 by the Faculty of Pharmacy, Mahidol University, Thailand. In 2017, the journal was renamed the Pharmaceutical Sciences Asia (PSA) journal. The PSA journal is an international peer-reviewed journal in English and committed to the timely publication of innovative articles and reviews. Since 2021, this journal is currently available only in an electronic format on the website: https://pharmacy.mahidol.ac.th/journal/. In addition, a doubleblinded peer-review system has been implemented via an online system to ensure high-quality work. To accelerate the publication process, the PSA journal has increased the issue numbers per year from quarter to six issues since January, 2021.